2008
DOI: 10.1038/modpathol.2008.91
|View full text |Cite
|
Sign up to set email alerts
|

HPV DNA detection and genotyping in 21 cases of primary invasive squamous cell carcinoma of the vagina

Abstract: Primary invasive squamous cell carcinoma of the vagina is rare, and the role of human papilloma virus in its pathogenesis remains unclear. The aims of our study were to determine the distribution of human papilloma virus genotypes in 21 cases of primary invasive squamous cell carcinoma of the vagina and to correlate human papilloma virus genotype with histological subtypes. Patients' clinical records were reviewed for demographic data and the stage of the disease. Tumors (n ¼ 21) were classified according to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
18
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 28 publications
7
18
2
Order By: Relevance
“…Human papillomavirus positivity was detected in 43% of the patients with PCV in our study, which is slightly lower compared with previously reported data from meta-analyses (Smith et al , 2009) and other studies (Ferreira et al , 2008; Insinga et al , 2008; De Vuyst et al , 2009; Fuste et al , 2010; Brunner et al , 2011; Alonso et al , 2012; Larsson et al , 2013), with a prevalence ranging between 51.4% and 81%. This variation is most likely due to differences in the detection methods used and in the selection of patients, but the geographical variation in HPV prevalence is another possibility.…”
Section: Discussioncontrasting
confidence: 86%
“…Human papillomavirus positivity was detected in 43% of the patients with PCV in our study, which is slightly lower compared with previously reported data from meta-analyses (Smith et al , 2009) and other studies (Ferreira et al , 2008; Insinga et al , 2008; De Vuyst et al , 2009; Fuste et al , 2010; Brunner et al , 2011; Alonso et al , 2012; Larsson et al , 2013), with a prevalence ranging between 51.4% and 81%. This variation is most likely due to differences in the detection methods used and in the selection of patients, but the geographical variation in HPV prevalence is another possibility.…”
Section: Discussioncontrasting
confidence: 86%
“…In this multicenter study which spanned 11 years , of the 60 samples examined, 75% were HPV positive, much higher than most previously published results 8,10,14-16 . Ostrow et al 8 found HPV in 21% of 14 patients by using in situ hybridization.…”
Section: Discussioncontrasting
confidence: 53%
“…Using southern blot hybridization, Ikenberg et al , found 55% of 18 patients positive for HPV 10 . Koyamatsu and colleagues 15 and Ferreira et al 16 both used polymerase chain reaction for detection and found HPV in 53% and 81% of 40 and 21 patients, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…1,[4][5][6][7] Previous studies regarding HPV types in VAIN and vaginal cancer or comparisons of HPV types between incident vaginal and previous cervical lesions were limited by small sample sizes and inconsistent conclusions. 3,4,[8][9][10][11][12][13][14][15] Smith et al 8 published a systemic review of 725 abstracts, in which the HPV detection rates among 166 cases of VAIN2/3 and 66 cases of VAIN1 were 92.6% and 98.5%, respectively. Another systemic review of 22 U.S. studies found HPV16/18 to be the predominant type in VAIN3 (n ¼ 97, 65.1%).…”
mentioning
confidence: 99%